Acoustic diffusion of a rotating composite elastic medium subjected to thermal source - Khaled Lotfy; Ibrahim S. Elshazly; Borhen Halouani; Praveen Ailawalia; Alaa A. El-Bary (AIP Advances)
This research is mainly concerned with understanding the propagation behavior of waves within complex elastic media, which leads to improving the properties of elastic materials to benefit from them practically. This research investigates the interaction between acoustic waves and thermal sources in a rotating elastic medium. The effect of the spread of the concentration of the substance through a chemical action is considered. The mathematical model was solved using the harmonic technique for waves in two dimensions to set the complete solutions of some basic physical quantities, such as temperature, displacement, and mechanical stress, as a linear solution in distance. Some appropriate boundary conditions were applied to the free surface to determine some unknown parameters. Linear solutions are represented graphically to discuss the propagation of waves for the dimensionless fundamental quantities under study. The results we obtained were discussed theoretically under the influence of some different parameters through two-dimensional graphs during some comparisons. To improve elastic material properties, specifically in their interaction with thermal sources and chemical actions within a rotating medium.